Pengembangan Video Animasi Pembelajaran Berbasis Powtoon pada Materi Ekosistem Kelas VII SMP Negeri 6 Palopo - Yunus, Nur Muhajirah; Khaerati; Rismawati (Jurnal Biogenerasi, 2023)
This study aims to determine the validity, practicality, and effectiveness of powtoon-based learning animation videos on Ecosystem material class VII at SMP Negeri 6 Palopo. This type of research is Research and Development (R&D) which refers to the ADDIE development research design which consists of five stages, namely analysis, design, development, implementation, and evaluation. The population of this study were all class VII students of SMP Negeri 6 Palopo. The sample in this study was class VII C. The results showed that the development of powtoon-based learning animation videos on Ecosystem material showed that: (1) the results of the validity test on powtoon-based learning media obtained a percentage of 85% with valid criteria; (2) the results of the practicality test by the teacher obtained a percentage of 92.5% with very practical criteria; (3) the results of the practicality test by students obtained a percentage of 82% with practical criteria; (4) the results of the effectiveness test obtained a percentage of 81.25% with effective criteria. Therefore, it can be concluded that powtoon-based learning animation videos meet the criteria to be used as science learning media, especially in Ecosystem material.